2022
DOI: 10.1038/s41420-022-00973-y
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the hyaluronic acid pathway induces M1 macrophages polarization via STAT1 in glioblastoma

Abstract: Immunosuppressive tumor microenvironment is a crucial factor that impedes the success of tumor immunotherapy, and tumor-associated macrophages (TAMs) are essential for the formation of tumor immunosuppressive microenvironment. Hyaluronic acid (HA) is highly important brick for glioblastoma microenvironment, but whether it contributes to TAM polarization and glioblastoma immunosuppressive microenvironment is less well known. In our study, we observed that disrupting glioblastoma HA synthesis or blocking HA bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Altogether, failure to upregulate MMP9 and reduction in pro-inflammatory cytokines indicate an altered pro-tumorigenic polarization of CD44 -/- myeloid cells in response to GBM. In agreement with this, a recent study has found that HA synthetized by glioma cells binds CD44 on myeloid cells thereby triggering their immunosuppressive polarization ( 55 ). Authors showed that by blocking CD44 on macrophages, the latter acquire an M1 phenotype resulting in reduced glioma proliferation and migration and increased survival of tumor-bearing mice.…”
Section: Discussionsupporting
confidence: 64%
“…Altogether, failure to upregulate MMP9 and reduction in pro-inflammatory cytokines indicate an altered pro-tumorigenic polarization of CD44 -/- myeloid cells in response to GBM. In agreement with this, a recent study has found that HA synthetized by glioma cells binds CD44 on myeloid cells thereby triggering their immunosuppressive polarization ( 55 ). Authors showed that by blocking CD44 on macrophages, the latter acquire an M1 phenotype resulting in reduced glioma proliferation and migration and increased survival of tumor-bearing mice.…”
Section: Discussionsupporting
confidence: 64%
“…Notably, the interaction of CD44 with HA is also regulated by a variety of cytokines such as IL-2, tumor necrosis factor (TNF), and chemokines, which activates CD44 to enhance the HA-CD47 interaction ( 41 ). A recent study shows that disruption of tumor HA synthesis or blocking HA binding to CD44 on TAM effectively increased the proportion of M1-TAMs by upregulating SIRPα ( 42 ). Besides, HA also binds to other receptors such as TLR4, which inhibit the lipopolysaccharide-induced activation of inflammatory macrophages or monocytes ( 43 ).…”
Section: Strategies To Reeducate Tamsmentioning
confidence: 99%
“…The M0 phenotype is considered an attenuated M2 phenotype, which is associated with tumor immunosuppression [ 24 ]. M1 macrophages and activated NK cells can inhibit tumor progression [ 25 , 26 ]. In summary, these observations indicated that GBM patients with high risk scores were more likely to have an immunosuppressive microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, patient risk scores were negatively correlated with M1 macrophage and activated NK cell infiltration and positively correlated with M0 macrophage infiltration. M1 macrophages can produce proinflammatory factors, which are thought to be associated with tumor suppression [ 25 ]. The M0 phenotype is considered the attenuated M2 phenotype, while the M2 phenotype is considered associated with tumor angiogenesis and the formation of a tumor immunosuppressive microenvironment [ 24 ].…”
Section: Discussionmentioning
confidence: 99%